Updating The Mother: Contemporary Intermedial Approaches to Brecht’s 1931 “Learning Play” - Power, Amber (Journal of the Motherhood Initiative for Research and Community Involvement, 2024)
This article argues for the continuing relevance of Bertolt Brecht’s 1931 “learning play,” The Mother, through a comparative assessment of two of its recent productions by experimental performance collectives My Barbarian (in 2013) and The Wooster Group (in 2021-22). Through analyzing the productions’ respective intermedial performance strategies, this article explores how both collectives use Brecht’s century-old play to address contemporary social and political challenges while privileging motherhood as a powerful mode of resistance.